Persuasion through artifacts- Sociological and psychological dimensions - Stroe, Mihaela (International Review, 2015)
Research suggests that applicants use various impression management tactics duringemployment interviews to influence interviewers’ evalutions of their performance. Yet, littleresearch has examined inteviewers/ perceptions of applicant’s impression management andtheir degree of nonverbal influence.This PhD study examines these questions, using both quantitative and qualitative data:Do interviewers accurately perceive applicant’s impression management tactics? How arethese perceptions integrated into their evaluations of applicant’s nonverbal behaviour? Isperception accuracy influenced by artifacts (professional clothing) that interviewees wear?It has cross-cultural design, because describes the differences in EuropeanCommission interviewers’ social perceptions and Romanian human resources managers onone hand, and between social perceptions of European Commission public servants andRomanian employees on the other hand, concerning 12 key concepts: persuasion, firstimpressions, professional image, credibility, authenticity, competence, self- confidence,self-management, self-presentation, self-promotion, impression management tactics,professional appearance